Study on the influencing factors and default risk of government debt. Issue 6 (3rd October 2017) - Guo, Jian-Hua
Abstract: Taking Chinese SY city as an example and by using the step-wise regression method, this paper firstly analyzed the influencing factors of the size of government debt. Then the BS model and naive model were used to study the default risk of government debt in SY city. The research results show that the level of economic development and local government fiscal revenue have a positive impact on the control of debt risk, while local government fiscal expenditure and debt holding subject structure and the total structure of the debt risk control have a negative impact. Finally, this paper put forward some suggestions on how to construct a reasonable tax revenue system for local government to optimize the main structure of government debt and control the total amount of government debt to solve the government debt risk.